Pelaksanaan Perjanjian Kerjasama Pembuatan Dokumen Amdal oleh PT Alas Sanggoro Yasa Consultans dengan Pemerintah Kota Pariaman dalam Pembangunan Rumah Sakit Umum Daerah (Rsud) Dr. Sadikin - Imran, Siti Lauriyanti; Rembrandt, Rembrandt; Mannas, Yussy Adelina (UNES Law Review, 2023)
One of the many constructions undertaken by the Government is in the City of Pariaman, which is the public infrastructure of a hospital called the Regional General Hospital (RSUD). The authority in this case is the government party that holds goods/services with both parties as the executor of procurement of goods /servicing government is PT. Sanggoro Yasa Consultans, where the cooperation between the two sides is then merged into a Cooperation Agreement (PKS). The objective of cooperation is related to the creation of environmental documentation namely environmental impact analysis (AMDAL) as one of the conditions that must be met for the Government of Pariaman to build RSUD dr. In accordance with the provisions in force. Implementation of the agreement of cooperation in the creation of documents AMDAL by PT Alas Sanggoro Yasa Consultans with the Government of the City of Pariaman in its implementation there are some problems and obstacles faced The agreement is made under the hands so that if made authentically then can provide legal certainty to both parties, and can be a powerful tool of evidence if there is a disadvantage. In its implementation, the factor affecting the failure to perform the agreement is its payment without advance, and Its implementation starts on September 8, 2020 and ends on December 18, 2020. However, at the time of performance by the debtor suffered payment delay until May 3, 2021. The authority in the implementation of the agreement is that there is a delay in payment due to APBD that has not fallen or has closed the book in 2020 so that APBD funds can not be disbursed by the Government of Pariaman City.